Contribuições da teoria do ensino desenvolvimental para a formação do conceito de cálculo de área no 5º ano do ensino fundamental - Brito, Luciene Santana de Souza (2020)
This qualitative research linked to the Research Line Theories of Education and Pedagogical Processes, of the Graduate Program in Education - PPGE of PUC Goiás has as its main theme the formation of the mathematical concept of calculating the area of flat figures in the 5th year of the through the study activity, organized based on the foundations of the Theory of Developmental Education. The problem issue sought to clarify what are the contributions of the study activity, organized based on the Theory of Developmental Teaching, for the assimilation and expansion of knowledge about the theoretical concept of calculating the area of flat figures by 5th graders, observable in the development of a formative didactic experiment. Therefore, we sought to analyze how the organization of the study activity, based on developmental didactics, contributes to the formation of the theoretical concept of area calculation in the 5th year of elementary school; examine how the process of assimilation and expansion of the theoretical concept of area of flat figures can influence the psychic and social development of students; demonstrate the importance of the teacher's proper training of the early years on disciplinary and pedagogical knowledge so that he can positively play his role as mediator; know how the process of changes from ZDP to ZDR can favor the formation of the theoretical concept of area calculation in the 5th year. A formative didactic experiment was then carried out, developed in three phases, in which the diagnosis of reality was made to be studied and the elaboration and application of the didactic training system was developed. Therefore, it was found that the study activity, when properly organized, leads the student to capture the scientific development behind the process of constitution of the contents, providing learning in the general scientific way of operating this content and appropriate theoreticalscientific knowledge in the form of concepts. Therefore, among the contributions of the Theory of Developmental Teaching to the assimilation and expansion of knowledge about the theoretical concept of area calculation in the early years of elementary school, the theoretical foundation necessary for the organize the study activity of schoolchildren of the initial years, the creation of moments of interaction and mediation during classes, stimulation of students' interest in the content of calculating the area of flat figures, the recognition of the importance of the contents geometric for the different situations of daily life and favoring, through the teaching-learning process that goes from general to private, the overcoming of traditional methodologies of mathematics teaching and, thus, contributing to the effective development of students.metodologias tradicionais de ensino de matemática e, dessa forma, contribuindo para o efetivo desenvolvimento dos estudantes.